Conformational rearrangements upon start codon recognition in human 48S translation initiation complex. Issue 9 (30th April 2022) - Yi, Sung-Hui; Petrychenko, Valentyn; Schliep, Jan Erik; Goyal, Akanksha; Linden, Andreas; Chari, Ashwin; Urlaub, Henning; Stark, Holger; Rodnina, Marina V; Adio, Sarah; Fischer, Niels
Abstract: Selection of the translation start codon is a key step during protein synthesis in human cells. We obtained cryo-EM structures of human 48S initiation complexes and characterized the intermediates of codon recognition by kinetic methods using eIF1A as a reporter. Both approaches capture two distinct ribosome populations formed on an mRNA with a cognate AUG codon in the presence of eIF1, eIF1A, eIF2–GTP–Met-tRNAi Met and eIF3. The 'open' 40S subunit conformation differs from the human 48S scanning complex and represents an intermediate preceding the codon recognition step. The 'closed' form is similar to reported structures of complexes from yeast and mammals formed upon codon recognition, except for the orientation of eIF1A, which is unique in our structure. Kinetic experiments show how various initiation factors mediate the population distribution of open and closed conformations until 60S subunit docking. Our results provide insights into the timing and structure of human translation initiation intermediates and suggest the differences in the mechanisms of start codon selection between mammals and yeast.